2014
DOI: 10.1111/wrr.12153
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cell‐coated sutures enhance collagen depositions in sutured tissues

Abstract: Sutures are commonly used for surgical procedures and new sutures are being developed to improve wound healing. In the past decade, it has been extensively shown that mesenchymal stem cells (MSCs) have a wound healing potential. To benefit the overall wound healing process, we aimed to analyze the usage of pretreated sutures for improving the implantation of MSCs in the tissues. Our results firstly showed that suture pretreatments with gelatin, poly-L-lysine, and NaOH improved the adhesive strength of MSCs to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 40 publications
(74 reference statements)
1
8
0
1
Order By: Relevance
“…In accordance with our results, MSCs coated sutures showed to enhance collagen deposition in sutured tissues [ 46 ]. Suggesting that this could be indirectly mediated by MSCs through the release of soluble factors which stimulate collagen synthesis, or directly through the release of collagen by MSCs.…”
Section: Discussionsupporting
confidence: 92%
“…In accordance with our results, MSCs coated sutures showed to enhance collagen deposition in sutured tissues [ 46 ]. Suggesting that this could be indirectly mediated by MSCs through the release of soluble factors which stimulate collagen synthesis, or directly through the release of collagen by MSCs.…”
Section: Discussionsupporting
confidence: 92%
“…More recently, Reckhenrich et al reported biodegradable suture filled with ASCs showed equal distribution of cells across the filament with improved viability and increase metabolic activity of cells with release of cytokines from in vitro wound healing assay. Furthermore, sutures modified with mesenchymal stem cells showed abundant deposition of collagen alpha‐1(I) chain with rapid recovery on wound healing …”
Section: Recent and Emerging Trendsmentioning
confidence: 99%
“…Furthermore, sutures modified with mesenchymal stem cells showed abundant deposition of collagen alpha-1(I) chain with rapid recovery on wound healing. 156 Sutures with growth factors and/or stem cells can be used as a substitute to scaffolds in tissue engineering and regenerative medicine. Sutures as a carrier in cell therapy have advanced its clinical benefits with increased mechanical function of heart, tendon repair, tracheal anastomosis and wound healing with rapid recovery and tissue regeneration in short duration.…”
Section: Stem Cells Seeded Suturesmentioning
confidence: 99%
“…CG rats showed complete healing with a mean time of 14.75 days, DG rats had complete healing with a mean of 21.25 days and, in MSCDG rats, the healing process was completed on a mean time of 13.5 days. In view of the clinical evidence of improvement in the wound healing in animals treated with MSC, it is believed that the benefits for the quality of healing resulting from the use of mesenchymal stem cells may be better confirmed at evaluations carried out after 15 days, when a better cosmetic scar quality could be assessed by the organization of collagen deposition (ARGOLO-NETO et al, 2012;CASADO et al, 2014). In this study, the MSC therapy was effective in accelerating the healing process and increasing the formation of collagen fibers, similar to observed by CASADO et al (2014) andCHUNMENG et al (2004).…”
Section: Discussionmentioning
confidence: 99%
“…as well as have immunosuppressive activity (CHOI et al, 2006). In an attempt to minimize the damage caused by the chronic administration of nonsteroidal anti-inflammatory drugs, mesenchymal stem cells (MSC) have emerged as a promising therapeutic alternative (WU et al, 2007;CASADO et al, 2014). These cells can be transplanted into the lesional sites soon after the occurrence of tissue injury and can be applied in the undifferentiated state, being stimulated by the environment to later differentiate or undergo differentiation in culture before implantation (DEL CARLO et al, 2008).…”
Section: Introductionmentioning
confidence: 99%